Design of Experiments Screening Design Used to Optimize the Punching Process of Cable Ducts Made of Polymer Blend PC/ABS: A Recent Study - F. Noller, Sebastian; Heiler, Roland; Pfennig, Anja (New Approaches in Engineering Research Vol. 16, 2021)
Burr and film are common when punching cable ducts made of polycarbonate/acrylonitrile-butadiene-styrene (PC/ABS). Additional deburring processes are required as a result, which is reflected in the product price. The punching process is investigated in the following study using Design of Experiments to emphasize the relationship between the input variables (factors) and the output variables (quality characteristics). The punching process was examined, and the key factors were identified and rated using a Failure Mode and Effects Analysis (FMEA). The Pareto approach was then used to choose the rated factors. The Software Modde was used to define factor levels and a D-optimal screening test plan. Using illustrated evaluation catalogues, the resulting quality characteristics were categorically appraised. The quality-characteristic mathematical models were then optimized and evaluated. The findings show that clearance is the most important factor in all five quality criteria studied. It is interesting to note that for some quality characteristics a reduction of the clearance would be positive, whereas for some a reduction would be positive. Between these two boundaries, it is considered that an ideal clearance size exists. In addition to the clearance, a holding-down of the material, in the close vicinity of the punch-out, during the punching of PC/ABS is essential for good results.